Ответы и объяснения

2013-02-01T11:58:40+00:00
Лучший Ответ!
2013-02-01T14:51:27+00:00

С-18. Понятие \sqrt[3]{x}

______________________________________________________________________

 

Вариант 3

 

1.Найдите значение выражения:

 

a) \sqrt[3]{-512}+\sqrt[3]{4\frac{17}{27}}=\sqrt[3]{-64\times8}+\sqrt[3]{\frac{125}{27}}=\sqrt[3]{-4^{3}\times2^{3}}+\sqrt[3]{\frac{5^{3}}{3^{3}}}=-4\times2+\frac{5}{3}=-8+\frac{5}{3}=\frac{-24+5}{3}=-\frac{19}{3}=-6\frac{1}{3}

 

b) 4\sqrt[3]{5}-\sqrt[3]{625}-\sqrt[3]{\frac{5}{64}}=4\sqrt[3]{5}-\sqrt[3]{5^{3}\times5}-\frac{\sqrt[3]{5}}{4}=4\sqrt[3]{5}-5\sqrt[3]{5}-\frac{\sqrt[3]{5}}{4}=-\sqrt[3]{5}-\frac{\sqrt[3]{5}}{4}=\frac{-4\sqrt[3]{5}-\sqrt[3]{5}}{4}=-\frac{5\sqrt[3]{5}}{4}=-1,25\sqrt[3]{5}

 

 

2.Упростит выражение:

 

a)\sqrt[3]{2x}(\sqrt[3]{108x^{2}}-\sqrt[3]{62,5x^{2}})=\sqrt[3]{216x^{9}}-\sqrt[3]{125x^{3}}=\sqrt[3]{6^{3}x^{9}}-\sqrt[3]{5^{3}x^{3}}=6x^{3}-5x=x(6x^{2}-5)

 

b)(\sqrt[3]{a}+\sqrt[3]{2b})(\sqrt[3]{a^{2}}-\sqrt[3]{2ab}+\sqrt[3]{4b^{2}})=\sqrt[3]{a}^{3}+\sqrt[3]{2b}^{3}=a+2b    

 

 \\\формула суммы кубов